New perspectives on the paleogeographic context of the Late Paleozoic Ice Age in Southwest Gondwana: U–Pb ages and sedimentary provenance data from the Paganzo Basin, Argentina - Rolan, Julián David (2025)
This study presents the first detrital zircon U–Pb analysis alongside new petrographic data from the Jejenes Formation (Serpukhovian–Bashkirian), located on the southern margin of the Paganzo Basin, Argentina in Southwest Gondwana. The results were compared with previously published data from other synchronously deposited units to the north (Guandacol Formation) and northeast (Malanzán Formation). Notably, glacigenic deposits are present in both the Guandacol and Jejenes formations but absent in the Malanzán Formation. A sedimentary provenance analysis was conducted for the three units, highlighting similarities and differences among the depocenters, allowing for the reconstruction of the paleogeographic and topographic landscape of the Paganzo Basin during the Serpukhovian–Bashkirian time. The comparative analysis supports the idea of disconnection and isolation among the three depocenters with each unit recording predominantly proximal sources and the recycling of pre-Carboniferous substrate. Although certain similarities exist in the age distribution of the detrital zircon grains recorded for the Malanzán and Guandacol formations, this does not imply that the depocenters were connected or fed by the same source area. Instead, these successions were likely sourced from rocks with a similar geological history, resulting in comparable age distributions due to sediment recycling. Thus, the results support a conservative approach when estimating sedimentary provenance in ancient glacigenic deposits, emphasizing the need to evaluate local sediment sources. The absence of glacigenic deposits in the Malanzán Formation could be linked to a lower topography, linked to distinct tectonic histories in the Pie de Palo, Valle Fértil, and Chepes–Malanzán ranges, underscoring the role of tectonic inheritance in the distribution of glacial centers during the Late Paleozoic Ice Age.